SPEAKING ANXIETY ANALYSIS IN PUBLIC SPEAKING CLASS AT HASANUDDIN ISLAMIC INSTITUTE OF PARE - Dewi, Fatqu Rofiqoh (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
This study aims to explore the phenomenon of speaking anxiety among third-semester students enrolled in the Public Speaking course at the English Education Program of the Hasanuddin Islamic Institute of Pare. Speaking anxiety is a common challenge faced by students in language learning, particularly in public speaking contexts, and can significantly impact their academic performance, self-esteem, and overall engagement in classroom activities. Using a qualitative research approach, the study investigates the causes, manifestations, and impacts of speaking anxiety among six participants. Data were collected through three instruments: semi-structured interviews, classroom observations, and questionnaires. The findings revealed that speaking anxiety was influenced by several factors, including fear of negative evaluation, lack of preparation, and unfamiliarity with public speaking tasks. Anxiety manifested in physical symptoms such as sweating and trembling, as well as behavioral responses such as avoidance and hesitation. The impact of speaking anxiety was observed in students’ reduced participation, lower self-confidence, and decreased motivation. The study highlights the importance of creating a supportive classroom environment, implementing gradual exposure techniques, and fostering peer support to reduce anxiety. These findings contribute to understanding how speaking anxiety affects students in public speaking courses and suggest strategies for educators to address this issue effectively.